Lost Voices in Research: Exposing the Gaps in the Mental Capacity Act 2005. (June 2019) - Heywood, Rob; Ryan, Hayley; Killett, Anne; Langdon, Peter; Plenderleith, Yvonne; Shiggins, Ciara; Bunning, Karen
Despite laudable intentions, since its inception, the Mental Capacity Act 2005 of England and Wales (MCA) has proved to be a controversial piece of legislation. The majority of legal scholarship has concentrated on the problems created by the Act in relation to the treatment of incapacitated patients. However, there is an additional and somewhat unexplored dimension to the MCA, that of research. We argue here that the research provisions of the MCA are poorly drafted and do not provide an appropriate balance between protection and empowerment. We also assert that contrasting obligations and expectations are placed on different parties in the approval process, which creates a blurred sense of responsibility and a potential chilling effect.